PROFILE OF ANTIBIOTIC RESISTANCE AGAINST INFLUENZA IN ADULT PATIENTS: A CASE STUDY AT CITY HEALTH CENTER IN INDONESIA - RAMDHANI, DANNI; KUSUMA, SRI AGUNG FITRI; AZIZAH, SHINTA NUR; KHUMAIROH, IKA; BAP, HILARIUS; SEDIANA, DEDE (International Journal of Applied Pharmaceutics, 2022)
Objective: In developing countries, cases of Haemophilus influenzae (HI) resistance to levofloxacin, cefixime, and tetracycline have become a serious problem in clinical treatment. This study was conducted to determine the antibiotic resistance profile of HI from adult patient isolates and to provide guidelines for more effective clinical treatment in Indonesia. Methods: The patient isolate stock was rejuvenated, cultured on growth media and the Kirby-Bauer disc diffusion method was used to test for antibiotic susceptibility. Evaluation was guided by recommendations from the Clinical and Laboratory Standard Institute (CLSI). Results: A total of 643 isolates obtained from the respiratory tract isolated and identified 73 HI strains. The resistance rates of the HI isolates to tetracycline, cefixime, and levofloxacin were 10.54 %, 4.31%, and 5.67%. Conclusion: Cefixime showed more effective activity than levofloxacin and tetracycline to treat the HI strain.